Synthesis of Ln1-x-yMe'xMe''yMnO₃ (Ln:La, Nd; Me' and Me'':Sr, Pb) solid solutions using sol-gel method - Shitchkova, T.A.; Emello, G.G.; Bashkirov, L.A. (Functional Materials, 2006)
A sol-gel method has been developed to synthesize the binary system solid solutions of rare-earth elements manganites (1-x)La₀,₆Pb₀,₄MnO₃- xNd₀,₆(Sr₀,₇Pb₀,₃)₀,₄MnO₃ (x = 0, 0.5 and 1.0). X-ray investigations show that the formation of solid solution phase for all x was observed after annealing of xerogel powders (tablets) in air at 700°C for 1 h. At x = 0.5 and 1.0, the solid solutions have an orthorhombically distorted perovskite structure, whereas at x = 0 (pure La₀,₆Pb₀,₄MnO₃), the crystal lattice is hexagonal. The specific saturation magnetization at 100 K (σ₁₀₀) and the Curie temperature (Tc) for manganite solid solutions synthesized using the sol-gel method (annealing at 900-1100°C for 1 h) at any x exceed the corresponding characteristics of similar solid solutions obtained by ceramic method (after 6 h heating at 1200 K).